Ibn Khaldun’s Educational Paradigm: A Philosophical-Hermeneutical Perspective - Misbahul Arifin; Danil Hakim Maulidi; Muflihatul Maqfirah (Journal of Islamic Education and Pedagogy, 2026)
This study focuses on Ibn Khaldun’s perspective on the paradigm shift in education, particularly the transformation from classical traditions to modernity. The main objective of this research is to explore the relevance of Ibn Khaldun’s educational thought, as presented in al-Muqaddimah, to the development of contemporary education which demands an integration of traditional values with modern needs. The research employs a library-based method by examining the primary text al-Muqaddimah (Dar al-Fikr, 2001) and its English translation by Rosenthal (2015), complemented with secondary sources from international scholarly articles. Data were analyzed through a qualitative-hermeneutical approach, emphasizing textual interpretation and its correlation with the theory of paradigm shift. The findings reveal that Ibn Khaldun positions education as the core of civilization, criticizes excessive rote learning, emphasizes gradual and systematic learning, and views social transformation as a catalyst for educational change. The implication of this research is the urgency of reinterpreting classical intellectual heritage in order to formulate a curriculum that is more humanistic, integrative, and adaptive to global challenges. Furthermore, the study highlights the potential for integrating tradition and modernity in shaping sustainable Islamic educational policies.